Review of Fund Work on Trade. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
The Fund has responded to a number of recent challenges facing its members by stepping up its work on trade. The Fund's trade agenda has been shaped by both Executive Board guidance and demands on missions. The present report assesses the Fund's priorities in the trade area, takes stock of its work, and reviews the Fund's collaboration and division of labor with other institutions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet